Safety profile and long-term efficacy of very high-power short-duration (60–70 W) catheter ablation for atrial fibrillation: results of a large comparative analysis. Issue 2 (12th December 2022) - Popa, Miruna A; Bourier, Felix; Lengauer, Sarah; Krafft, Hannah; Bahlke, Fabian; Förschner, Leonie V; Dorfmeister, Stephan; Kathan, Susanne; Telishevska, Marta; Englert, Florian; Lennerz, Carsten; Reents, Tilko; et al.
Abstract: Aims: This retrospective study sought to compare complication rates and efficacy of power-controlled very high-power short-duration (vHPSD) and conventional catheter ablation in a large cohort of patients with atrial fibrillation (AF). Methods and results: We analyzed 1115 consecutive patients with AF (38.7% paroxysmal, 61.3% persistent) who received first-time catheter ablation at our centre from 2015 to 2021. Circumferential pulmonary vein isolation ± additional substrate ablation using an irrigated-tip catheter was performed with vHPSD (70 W/5–7 s or 60 W/7–10 s) in 574 patients and with conventional power (30–35 W/15–30 s) in 541 patients. Baseline characteristics were well-balanced between groups (mean age 65.1 ± 11.2 years, 63.4% male). The 30-day incidence of cardiac tamponade [2/574 (0.35%) vs. 1/541 (0.18%), P = 0.598], pericardial effusion ≥ 10 mm [2/574 (0.35%) vs. 1/541 (0.18%), P = 0.598] and transient ischaemic attack [1/574 (0.17%) vs. 2/541 (0.37%), P = 0.529] was not significantly different between vHPSD and conventional ablation. No stroke, atrio-esophageal fistula, cardiac arrest or death occurred. Procedure (122.2 ± 46.8 min vs. 155.0 ± 50.5 min, P < 0.001), radiofrequency (22.4 ± 19.3 min vs. 52.9 ± 22.0 min, P < 0.001), and fluoroscopy (8.1 ± 7.2 vs. 9.2 ± 7.4, P = 0.016) duration were significantly shorter in the vHPSD group. At 12 months follow-up, freedom of any atrial arrhythmia was 44.1% vs. 34.2% ( P = 0.010) in persistent AF and 78.1% vs. 70.2% in paroxysmal AF ( P = 0.068). Conclusion: vHPSD ablation is as safe as conventional ablation and is associated with an improved long-term efficacy in persistent AF. Graphical Abstract: Graphical Abstract